DEVELOPING AN INTERACTIVE LEARNING MODEL USING VISUAL BASIC APPLICATIONS WITH ETHNOMATHEMATICAL CONTENTS TO IMPROVE PRIMARY SCHOOL STUDENTS’ MATHEMATICAL REASONING - Euis Eti Rohaeti; Nelly Fitriani; Padillah Akbar (Jurnal Infinity, 2020)
This study aims to examine the development of an interactive learning model using Visual Basic Application for Microsoft excel with ethnomathematical content on fractions, to improve primary school students’ mathematical reasoning abilities. The research method used is development through the stages of conducting preliminary studies and literature, designing interactive learning models, conducting FGDs, producing initial designs of interactive learning models, conducting limited trials in one primary school, making revisions, conducting extensive trials in four primary schools, producing trial in another primary school. The last obtaining a final model and conducting socialisation. The last, it provides a test of mathematical reasoning ability. The research subjects were teachers and students in six primary schools. The research instruments were interviews, validation sheets, documentation, learning observation sheets, questionnaires and mathematical reasoning ability test.  The assessment criteria for the developed learning model include syntax, social system, principle of reaction, supports system and instructional impact. The results showed that 1) Development of VBA-assisted and ethnomatematically-loaded interactive learning models go through two major stages, namely product development and validation  2) The Interactive learning model was declared very valid; 3) The responses of teachers and students were generally positive; 4) The achievement of students’ mathematical reasoning abilities after gave learning with an interactive model using VBA for Microsoft Excel with ethnomathematical contents better than using ordinary learning.